The Causes Of Sales Staff Turnover At Private News And Advertising Monitoring Company - Punkavanam, Mahalingam (2024)
This purpose of this study is to identify factors contributing towards turnover intention among the bank employee in Private news and advertising monitoring company. The turnover intention can be measured in the aspect of working conditions, pay and reward, recognition and growth opportunities. The survey method was used to collect primary data through the use of questionnaire to the employees attached at private news and advertising monitoring company located in Petaling Jaya. The study used a sample of 65 respondents drawn from the private news and advertising company Sales Staff from varying positions within the organization. The data was collected using questionnaires through self- administration. The latest version of the Statistical Package for the Social Sciences (SPSS) was used to perform analysis on the data. Based on the findings, there is no significant relationship between working conditions, pay and reward, and staff turnover intention. While, there is a significant relationship between recognition, growth opportunities and staff turnover intention. The study may have various practical implications such as the contribution to the strategies for creating human assets by using compensation management, as well as other ways to add value to human assets in order to reduce the employee’s turnover rates.